Pengaruh Retribusi Daerah, Dana Perimbangan Dan Belanja Modal Terhadap Kemandirian Keuangan Pemerintah Daerah: Studi Kasus Pada Kabupaten dan Kota di Provinsi Jawa Barat Tahun Anggaran 2019-2023 - Cahya, Alifia Aprilianti; Ridwan, Ridwan (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
The research aims to investigate the impact of regional compensation, equalization funds, and capital investment on local financial autonomy across 13 regencies in West Java Province from 2019 to 2023. Regional financial independence is a vital metric used to assess a region's capacity to finance its governance without relying heavily on central government assistance. The study adopts a quantitative method with both descriptive and verification approaches. Purposive sampling technique was used, selecting 13 out of 27 available regencies and cities. Classical assumption tests, including a normality assessment using the Kolmogorov–Smirnov technique, yielded a significant result (Sig.=.055). The outcome of the simultaneous significance test (F-test) indicates that, simultaneously, regional retribution, balancing funds, and capital expenditure significantly affect regional financial independence (Sig.=.011). However, the t-test findings show that only balancing funds and capital expenditure have a significant individual effect, while regional retribution does not. The adjusted coefficient of determination (Adjusted R² = .047) suggests that the selected independent factors in the regression model account for only 4.7% of the variation in regional financial independence, with the remaining variation explained by other external factors. These findings suggest that local governments should prioritize the effective management of equalization funds and capital expenditures to promote sustainable regional financial independence